DEVELOPMENT OF EDGE AND DELIVERY SUBSYSTEM FOR INTRUSION DETECTION SYSTEM IN CYBER- PHYSICAL SYSTEM - Ananda Dotty, Fadel
Cyber-Physical Systems (CPS) are system that can integrate computational capabilities in digital world to control physical processes in the real world. Some CPS are safety critical, and attacks on these systems could have significant impacts such as environmental damage and loss of human lives. One prominent attack on CPS was the Stuxnet attack, which targeted Iran’s nuclear centrifuges. This highlights the importance of protecting CPS from such attacks. Intrusion Detection System (IDS) is a system that can be used to safeguard CPS. Several studies have proposed IDS detection methods for CPS using machine learning approaches based on provided data. Typically, these studies utilize existing CPS datasets or data from other components, such as electromagnetic side-channel emissions. However, they lack detailed explanations on how to acquire data from CPS or other components for IDS purposes, as well as the response mechanisms in case the IDS itself comes under attack. This thesis discusses methods for obtaining CPS data for IDS and proposes response strategies when an attack is detected by the IDS. Data acquisition from CPS can be achieved through CPS components (sensors and actuators) or the control layer of CPS (PLC). The chosen solution involves directly obtaining analog data from CPS components, which can be used for attack detection in the IDS. The CPS response solution involves simulating the activation or deactivation of the CPS based on valid commands.